2022
DOI: 10.38094/jlbsr30261
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterisation of Carbapenemase-Producing Acinetobacter baumannii isolates from Hospitalised Patients in Iraq

Abstract: Carbapenem-resistant Acinetobacter baumannii has been considered one of the major threats to patients worldwide. To evaluate carbapenemase in several clinical isolates using phenotypic and genotypic approaches. A total of 49 A. baumannii isolates were tested against imipenem and meropenem discs on Muller Hinton agar, then screened phenotypically through the modified Hodge test (MHT), combined disc test (CDT) and modified carbapenem inactivation method (mCIM). The tested isolates have been subjected to polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…In addition to this, alarmingly high levels of resistance (92%) to imipenem and meropenem among A. baumannii calcoaceticus complex was recorded in 2016 among isolates obtained from a number of different hospitals located in two cities within the Kurdistan region of Iraq [33]. Recently, researchers in 2019 recorded MDR-AB in 73.3% of their isolates in Hilla [34], other studies which were conducted during 2020 in Ninawa reported 100% [35] and in Duhok during 2022 recorded 96% [36]. About 38.7% of our isolates were XDR, similar data (30%) was recorded by Radhi and Al-Charrakh in 2019 [34], while other researchers found much higher XDR result (84.2%) in Ninawa during 2020 [35], The Taiwan Surveillance of Antimicrobial Resistance program found that from 2002 to 2010, the frequency of the XDR A. baumannii jumped from 1.3% in 2002 to 41.0% in 2012.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to this, alarmingly high levels of resistance (92%) to imipenem and meropenem among A. baumannii calcoaceticus complex was recorded in 2016 among isolates obtained from a number of different hospitals located in two cities within the Kurdistan region of Iraq [33]. Recently, researchers in 2019 recorded MDR-AB in 73.3% of their isolates in Hilla [34], other studies which were conducted during 2020 in Ninawa reported 100% [35] and in Duhok during 2022 recorded 96% [36]. About 38.7% of our isolates were XDR, similar data (30%) was recorded by Radhi and Al-Charrakh in 2019 [34], while other researchers found much higher XDR result (84.2%) in Ninawa during 2020 [35], The Taiwan Surveillance of Antimicrobial Resistance program found that from 2002 to 2010, the frequency of the XDR A. baumannii jumped from 1.3% in 2002 to 41.0% in 2012.…”
Section: Discussionmentioning
confidence: 95%
“…Following the manufacturer's instructions, blood agar and MacConkey agar plates (Sigma-Aldrich) were produced, and Acinetobacter species were grown on these media for 18 to 24 hours at 37 ºC. After the incubation period of one night, the isolates of Acinetobacter species were verified through Gram staining and biochemical tests, which included the VITEK 2 system as instructed by the manufacturer (BioMérieux), the Catalase test, the Citrate utilization test, the Indole test, the Oxidase test, the Motility test, the Triple Sugar Iron (TSI) agar test, and the Urease test [21][22][23][24].…”
Section: Confirmatory Tests Of Isolatesmentioning
confidence: 99%
“…On the epidemiology of A. baumannii and other infections in hospitalized patients in Iraq, however, few studies have been released (15). Additionally, limited molecular typing techniques have been used in earlier research from Iraq, which is crucial for obtaining reliable epidemiological data and understanding the spread of the organism (16)(17)(18). To determine the sequence type, genetically define the carbapenem resistance phenotype, and clarify the epidemiology of MDR A. baumannii in Kurdistan region of Iraq, the Oxford MLST scheme was used in the current work.…”
Section: Multilocus Sequence Typing Analysis and Molecular Characteri...mentioning
confidence: 99%